Tinjauan Moralitas Hukum terhadap Overkriminalisasi dalam Regulasi Digital Indonesia - Khaila Aurellia; Irwan Triadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Legal uncertainty within Indonesia's digital regulation has triggered significant tension between state law enforcement and public morality dynamics. This study aims to analyze the juridical implications of vague formulations (deficit of lex certa principle) in the Electronic Information and Transactions Law (UU ITE), which lead to overcriminalization, and its impact on the emergence of Cancel Culture as an alternative punishment mechanism. Employing normative legal research with statutory and conceptual approaches, this study examines the coherence between the formal validity of positive law and the principles of the internal morality of law. The main findings indicate that the ambiguity of provisions regarding indecency and defamation in the UU ITE has granted excessive discretion to law enforcement officials to criminalize subjective morality without indicators of tangible harm. This failure of the law to provide substantive justice is subsequently responded to by society through Cancel Culture, which ironically violates the principle of due process of law. The novelty of this research lies in the synthesis that the crisis of digital law enforcement is not merely an implementation issue but a structural moral defect due to the neglect of the lex certa principle. As a concrete solution, this study recommends revising the UU ITE by converting formal offenses into material offenses that require tangible harm to restore legal legitimacy.